Small town South Africa: the historical geography of selected Eastern Cape towns and current development initiatives within them - White, Richard Charles Crookes (Rhodes University, Faculty of Science, Department of Geography, 2004)
Small towns can be seen as the fundamental building blocks of tbe urban system. Through time, some of these towns have lost the primary reason for their existence. Some towns that have been declining or stagnating include old mining and industrial towns, such as Indwe in the Eastern Cape or Welkom in the Free State. Some towns have also changed the main focus of tbeir economy, for example, from that of mining to that of tourism, as in the case of Utrecht in Kwa-Zulu Natal (Nel, 2002). In light of the above, this thesis seeks to critically evaluate what has happened in selected small towns in the Eastern Cape. The research investigated a number of towns in the Eastern Cape, looking at the history and influence of colonisation, population dynamics, education levels, employment opportunities, migration and the influence of capitalism on the economic and social structure of the town, as well as tbe evolution of its economy. The research sample consisted of interviews witb local historians, community leaders, development agencies and individuals who were benefiting from tbe various development initiatives/project in the towns. These interviews, in conjunction with the literature identified, were conducted in the selected small towns, assessing whether development was succeeding and, in conclusion, identifying witb reference to the study sites, what was learnt. The research process generated a number of lessons that need to be taken into consideration when attempting social and economic upliftment in small towns. These include: the need for leadership, support from the local population and the need for financial assistance to support and uplift the community.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Cities and towns -- South Africa -- Eastern Cape -- Growth; Cities and towns -- South Africa -- Population -- Statistics; Economic development -- South Africa -- Eastern Cape; Community development -- South Africa -- Eastern Cape; Eastern Cape (South Africa) -- History; Eastern Cape (South Africa) -- Economic conditions; Eastern Cape (South Africa) -- Social conditions